Rapid phasic activity of ventral pallidal neurons during cocaine self-administration - Root, David H. (2010)
Little is known regarding the involvement of the ventral pallidum (VP) in cocaine-seeking behavior, in contrast with considerable documentation of the involvement of its major afferent, the nucleus accumbens, over the past thirty years utilizing electrophysiology, lesion, inactivation, molecular, imaging, and other approaches. The VP is neuroanatomically positioned to integrate signals projected from the nucleus accumbens, basolateral amygdala, and ventral tegmental area. In turn, VP projects to thalamoprefrontal, subthalamic, and mesencephalic dopamine regions having widespread influence across mesolimbic, mesocortical, and nigrostriatal systems. Prior lesion studies have implicated VP in cocaine-seeking behavior, but the electrophysiological mechanisms underlying this behavior in the VP have not been investigated. In the present investigation, following two weeks of training over which animals increased drug intake, VP phasic activity comprised rapid-phasic increases or decreases in firing rate during the seconds prior to and/or following cocaine-reinforced responses, similar to those found in accumbens. As a population, the direction (increasing or decreasing) and magnitude of firing rate changes were normally distributed suggesting that ventral striatopallidal processing is heterogeneous. Since changes in firing rate around the self-administering lever press occurred in animals that escalated drug intake prior to neuronal recordings, a marker of “addiction-like behavior” in the rat, the present experiment provides novel support for a role of VP in drug-seeking behavior. This is especially important given that pallidothalamic and pallidomesencephalic VP projections are positioned to alter dopaminoceptive targets such as the medial prefrontal cortex, nucleus accumbens, and dorsal striatum, all of which have roles in cocaine self-administration.